MARKETING IN THE AGE OF AI: HARNESSING TECHNOLOGY TO UNDERSTAND CONSUMER BEHAVIOR - Miko Andi Wardana; Mohamad Sajili; Helendra Helendra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The integration of artificial intelligence (AI) in marketing has significantly altered how businesses understand and interact with consumers. This study aims to explore how AI can enhance consumer behavior analysis and optimize marketing strategies through advanced predictive and personalization technologies. Employing a qualitative approach, data were collected through semi-structured interviews with marketing professionals and secondary data from industry reports. Thematic analysis was used to analyze findings, revealing that AI enables marketers to predict consumer needs, segment audiences more effectively, and provide highly personalized interactions. The results indicate that AI-driven personalization not only increases customer engagement but also fosters long-term loyalty. Furthermore, this research highlights the need for ethical considerations in AI use, such as data privacy, to maintain consumer trust. These findings offer valuable insights for businesses aiming to leverage AI for more effective and consumer-centered marketing strategies. Future research is suggested to examine the ethical implications of AI in marketing across diverse industries.